Bilateral osteochondrosis of the distal tibial epiphysis: a case report and review of the literature - Aye, Victor; Pilloux, Maxime; Paris, Elio; Fasel, Dimitri; De Marco, Giacomo; Vazquez, Oscar; Steiger, Christina; Dayer, Romain; Boudabbous, Sana; Ceroni, Dimitri (Frontiers in Pediatrics, 2025)
Osteochondrosis of the distal tibial epiphysis is a rare condition, and its clinical presentation thus remains poorly defined. The few reported cases in the literature suggest an insidious, progressive onset of ankle pain and swelling with no clear history of trauma. Imaging is crucial to diagnosis, with radiographs typically revealing epiphyseal irregularities, fragmentation and sclerosis, whereas magnetic resonance imaging enables the early detection of bone marrow oedema, subchondral fractures and cartilage abnormalities. We report on an 11.5-year-old boy presenting with a history lasting for more than 12 months of left ankle pain and bilateral osteochondrosis of the distal tibial epiphysis. The etiology of distal tibial osteochondrosis remains unclear, with proposed mechanisms including vascular disorders, repetitive microtrauma and genetic predisposition. The condition's rarity, particularly in the bilateral form, suggests a multifactorial pathogenesis going beyond mechanical stress alone. Its prognosis depends on the degree of epiphyseal involvement and the presence of premature physeal closure, emphasizing the importance of early diagnosis and tailored management strategies. Based on this rare case, we summarize more than 75 years of observations of patients with osteochondrosis of the distal tibial epiphysis, discuss its etiology and revise information about its known clinical features, radiological characteristics, pathogenesis and treatment.